High-strength steel plate

JP7640906B2Active Publication Date: 2025-03-06NIPPON STEEL CORPORATION
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023539733
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-02
Filing Date
2022-07-12
Publication Date
2025-03-06
Estimated Expiration
2042-07-12

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、改善された曲げ加工性を有しかつ疵の発生についても抑制可能な高強度鋼板を提供することができる。このような高強度鋼板は、疵の発生に対する抵抗性が高く、外観性状を良好に維持することができるため、例えば自動車の特に準外板部品と呼ばれる高い強度とともに意匠性や外観性が求められるピラー部材のような骨格部材としての使用に非常に有用である。また、このような高強度鋼板は、表面硬さが高くそれゆえ耐摩耗性にも優れるため、例えば建設機械用クレーンのブームなど、高強度に加えて、高い曲げ加工性及び耐摩耗性が求められる用途においても非常に適している。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640906000001
    Figure 0007640906000001
  • Figure 0007640906000002
    Figure 0007640906000002
  • Figure 0007640906000003
    Figure 0007640906000003
Patent Text Reader

Abstract

Provided is a high-strength steel sheet including a plate thickness center section and a surface layer soft section formed on one or both sides of the plate thickness center section, wherein: the plate thickness center section has a prescribed chemical composition and a microstructure including 85% or more tempered martensite; the surface layer soft section has a thickness of more than 10 μm but not more than 5% of the plate thickness, has a microstructure including 80% or more ferrite, and includes an internally oxidized layer having a thickness of 3 μm or more from the surface; the average Vickers hardness (Hc) of the plate thickness center section and the average Vickers hardness (Hs) of the surface layer soft section satisfy Hs / Hc≤0.50; and the void area percentage is 3.0% or less in the region from the surface up to the 10 μm depth position.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high strength steel plate. [Background technology]

[0002] Increasing the strength of a steel plate reduces its workability, so it is generally difficult to achieve both strength and workability in a steel plate. For example, booms of cranes for construction machinery tend to be longer in accordance with the recent trend toward taller buildings, and therefore there is a demand for lightweight and high strength. In addition, when steel plates are applied to members such as booms, bending is performed, so there is an increasing need for high-strength steel plates with excellent bending workability.

[0003] In the automotive industry, there is a demand for lighter car bodies in order to improve fuel efficiency. In order to achieve both lighter car body weight and crashworthiness, one effective method is to increase the strength of the steel plates used, and against this background, the development of high-strength steel plates is being promoted. In general, high-strength steel plates have poorer formability, such as bending workability, than mild steel plates, and forming methods used for mild steel plates may not be applicable. Therefore, in the field of automotive steel plates, there is a high demand for high-strength steel plates with excellent bending workability.

[0004] Patent Document 1 describes a high-strength steel plate having a plate thickness center and a soft surface portion formed on one or both sides of the plate thickness center, in which the metal structure of the plate thickness center contains, in area ratio, 85% or more of tempered martensite, the metal structure of the soft surface portion contains, in area ratio, 65% or more of ferrite and 5% or more but less than 20% of pearlite, the average spacing between pearlite in the soft surface portion is 3 μm or more, and the Vickers hardness (Hc) of the plate thickness center and the Vickers hardness (Hs) of the soft surface portion satisfy 0.50≦Hs / Hc≦0.75. Patent Document 1 also describes that the bending load and bendability of the steel plate can be increased simultaneously by distributing pearlite as a hard structure in the soft surface portion.

[0005] Patent Document 2 describes a high-strength steel plate having a tensile strength of 800 MPa or more, including a plate thickness center and a surface-softened portion disposed on one or both sides of the plate thickness center, wherein each surface-softened portion has a thickness of more than 10 μm to 30% or less of the plate thickness, the average Vickers hardness of the surface-softened portion is 0.60 times or less the average Vickers hardness at the 1 / 2 position of the plate thickness, and the standard deviation of the nano-hardness of the surface-softened portion is 0.8 or less. Patent Document 2 also teaches that in addition to having a surface-softened portion, bending property is significantly improved by suppressing the hardness variation of the surface-softened portion.

[0006] Patent Document 3 describes a high-strength hot-rolled steel sheet having a predetermined chemical composition, 90% or more of the structure being martensite, and having an average aspect ratio of prior austenite grains from the surface layer to 1 / 8 of the plate thickness in a cross section in the rolling direction of 3 to 20. Patent Document 3 also describes that the above configuration makes it possible to provide a high-strength hot-rolled steel sheet having excellent bending workability and wear resistance and a yield strength of 950 MPa or more.

[0007] Patent Documents 4 to 10 describe high-strength plated steel sheets having a hot-dip galvanized layer or an alloyed hot-dip galvanized layer on the surface of a base steel sheet, the high-strength plated steel sheets having, in the order from the interface between the base steel sheet and the plated layer toward the base steel sheet side, an internal oxide layer containing at least one oxide selected from the group consisting of Si and Mn, a layer containing the internal oxide layer, and a soft layer having a Vickers hardness that satisfies 90% or less of the Vickers hardness at a t / 4 portion of the base steel sheet, where t is the sheet thickness of the base steel sheet, and a predetermined hard layer, the soft layer having an average depth D of 20 μm or more and the internal oxide layer having an average depth d of 4 μm or more and less than D, and the high-strength plated steel sheets having a tensile strength of 980 MPa or more. Furthermore, Patent Documents 4 to 10 teach that hydrogen embrittlement can be effectively suppressed by controlling the average depth d of the internal oxidation layer to 4 μm or more and utilizing the internal oxidation layer as a hydrogen trapping site, and that bendability in particular can be improved by appropriately controlling the relationship between the average depth d of the internal oxidation layer and the average depth D of the soft layer including the region of the internal oxidation layer. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2020 / 196060 [Patent Document 2] International Publication No. 2018 / 151331 [Patent Document 3] JP 2014-227583 A [Patent Document 4] International Publication No. 2016 / 111271 [Patent Document 5] International Publication No. 2016 / 111272 [Patent Document 6] International Publication No. 2016 / 111273 [Patent Document 7] International Publication No. 2016 / 111274 [Patent Document 8] International Publication No. 2016 / 111275 [Patent Document 9] International Publication No. 2015 / 146692 [Patent Document 10] International Publication No. 2015 / 005191 Summary of the Invention [Problem to be solved by the invention]

[0009] As proposed in the prior art, it is possible to improve bending workability by disposing a soft layer on the surface of a steel sheet. On the other hand, disposing a soft layer on the surface of a steel sheet generally reduces the surface hardness, which may lead to deterioration of the appearance due to the occurrence of scratches and deterioration of the wear resistance. In this regard, Patent Document 3 teaches that by setting the average aspect ratio of the prior austenite grains from the surface layer to 1 / 8 of the plate thickness to 3 or more and 20 or less, the surface hardness can be improved and a steel sheet with excellent bending workability can be obtained. However, Patent Document 3 does not necessarily fully consider the structure control in the surface layer other than the average aspect ratio of the prior austenite grains, and therefore the invention described in Patent Document 3 still has room for improvement in terms of improving bending workability and surface hardness.

[0010] Therefore, an object of the present invention is to provide a high-strength steel sheet which has improved bending workability and is also capable of suppressing the occurrence of defects. [Means for solving the problem]

[0011] In order to achieve the above object, the present inventors have discovered that in a high-strength steel plate having a tensile strength of 1250 MPa or more, a soft surface portion having an average Vickers hardness that is a predetermined ratio relative to the average Vickers hardness at the center of the plate thickness can be provided to improve bending workability, and an internal oxide layer having a predetermined thickness can be formed at the outermost layer of the soft surface portion, and voids formed in the vicinity of the surface can be controlled within an appropriate range, thereby improving the surface hardness and suppressing the occurrence of defects on the steel plate surface, and have completed the present invention.

[0012] The present invention which has achieved the above object is as follows. (1) A high-strength steel plate including a plate thickness center portion and a surface soft portion formed on one or both sides of the plate thickness center portion, The thickness center portion is, in mass%, C: 0.10-0.30%, Si: 0.01 to 2.50%, Mn: 0.10-10.00%, P: 0.100% or less, S: 0.0500% or less, Al: 0-1.50%, N: 0.0100% or less, O: 0.0060% or less, Cr: 0-2.00%, Mo: 0-1.00%, B: 0~0.0100%, Ti: 0 to 0.30%, Nb: 0-0.30%, V: 0~0.50%, Cu: 0-1.00%, Ni: 0 to 1.00%, Ca: 0-0.040%, Mg: 0 to 0.040%, REM: 0~0.040%, and The balance is composed of Fe and impurities. The chemical composition satisfies 1.50≦[Si]+[Mn]+[Al]+[Cr]≦20.00, in which [Si], [Mn], [Al] and [Cr] are the contents (mass%) of each element, In terms of area ratio, Tempered martensite: A microstructure containing 85% or more of The surface soft portion has a thickness of more than 10 μm to 5.0% or less of the plate thickness, In terms of area ratio, Ferrite: Microstructure containing 80% or more The high-strength steel plate includes an internal oxide layer having a thickness of 3 μm or more from the surface thereof, The average Vickers hardness (Hc) of the plate thickness center portion and the average Vickers hardness (Hs) of the surface soft portion satisfy Hs / Hc≦0.50, A high-strength steel plate, wherein a void area ratio in a region from the surface of the high-strength steel plate to a depth of 10 μm is 3.0% or less. (2) The thickness center portion has an area ratio of Tempered martensite: 85% or more, At least one of ferrite, bainite, pearlite, and retained austenite: less than 15% in total; and The high-strength steel plate according to (1) above, having a microstructure consisting of as-quenched martensite: less than 5%. (3) The surface soft portion has an area ratio of Ferrite: 80% or more, At least one of tempered martensite, bainite, and retained austenite: less than 20% in total; Perlite: Less than 5%; The high-strength steel plate according to the above (1) or (2), having a microstructure consisting of less than 5% as-quenched martensite. (4) The high-strength steel plate according to any one of the above (1) to (3), further comprising a hot-dip galvanized layer, a galvannealed layer, or an electrolytic galvanized layer on a surface of the soft surface portion. Effect of the Invention

[0013] According to the present invention, it is possible to provide a high-strength steel sheet having improved bending workability and capable of suppressing the occurrence of defects. Such a high-strength steel sheet has high resistance to the occurrence of defects and can maintain good appearance properties, and is therefore very useful for use as, for example, quasi-exterior plate parts of automobiles, particularly as frame members such as pillar members which require high strength as well as design and appearance. In addition, such a high-strength steel sheet has high surface hardness and therefore excellent wear resistance, and is therefore very suitable for applications requiring high bending workability and wear resistance in addition to high strength, such as the booms of construction machinery cranes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <High strength steel plate> A high-strength steel plate according to an embodiment of the present invention includes a plate thickness center portion and a surface soft portion formed on one side or both sides of the plate thickness center portion, The thickness center portion is, in mass%, C: 0.10-0.30%, Si: 0.01 to 2.50%, Mn: 0.10-10.00%, P: 0.100% or less, S: 0.0500% or less, Al: 0-1.50%, N: 0.0100% or less, O: 0.0060% or less, Cr: 0-2.00%, Mo: 0-1.00%, B: 0~0.0100%, Ti: 0 to 0.30%, Nb: 0-0.30%, V: 0~0.50%, Cu: 0-1.00%, Ni: 0 to 1.00%, Ca: 0-0.040%, Mg: 0 to 0.040%, REM: 0~0.040%, and The balance is composed of Fe and impurities. The chemical composition satisfies 1.50≦[Si]+[Mn]+[Al]+[Cr]≦20.00, in which [Si], [Mn], [Al] and [Cr] are the contents (mass%) of each element, In terms of area ratio, Tempered martensite: A microstructure containing 85% or more of The surface soft portion has a thickness of more than 10 μm to 5.0% or less of the plate thickness, In terms of area ratio, Ferrite: Microstructure containing 80% or more The high-strength steel plate includes an internal oxide layer having a thickness of 3 μm or more from the surface thereof, The average Vickers hardness (Hc) of the plate thickness center portion and the average Vickers hardness (Hs) of the surface soft portion satisfy Hs / Hc≦0.50, The high-strength steel plate is characterized in that the void area ratio in a region from the surface to a depth of 10 μm is 3.0% or less.

[0015] As mentioned above, the bending workability can be improved by disposing a soft layer on the surface of a steel sheet, but on the other hand, the surface hardness generally decreases due to such a soft surface portion, which may lead to deterioration of the appearance due to the occurrence of scratches and deterioration of the wear resistance. Therefore, the present inventor conducted a study on a high-strength steel sheet having a tensile strength of 1250 MPa or more, focusing on the outermost layer and the structure near the surface in the soft surface portion, in addition to the soft surface portion provided on one or both sides of the center of the sheet thickness. More specifically, the present inventor first found that the bending workability of a high-strength steel sheet can be significantly improved by controlling the microstructure of the soft surface portion having a predetermined thickness to contain ferrite at an area ratio of 80% or more, and controlling the average Vickers hardness (Hs) of the soft surface portion and the average Vickers hardness (Hc) of the center of the sheet thickness so that they satisfy the formula Hs / Hc≦0.50. The present inventors also conducted further studies focusing on an internal oxide layer formed in the outermost layer of a steel sheet when components in the steel sheet that are relatively easily oxidized (e.g., Si, Al, etc.) combine with oxygen in the annealing atmosphere during annealing treatment performed after rolling (typically hot rolling and cold rolling), and voids (air gaps) that may be formed near the surface layer in relation to other manufacturing conditions. As a result, the present inventors found that by controlling the area ratio of voids formed near the surface layer, more specifically the void area ratio in a region up to a depth of 10 μm from the steel sheet surface to 3.0% or less while making the internal oxide layer containing oxides of Si, Al, etc. to a thickness of 3 μm or more from the steel sheet surface, the surface hardness of the steel sheet can be greatly improved and the occurrence of scratches on the steel sheet surface can be significantly suppressed.

[0016] Without intending to be bound by any particular theory, it is believed that the internal oxide particles present in the internal oxidation layer become obstacles to dislocations in the steel, thereby pinning the dislocation movement and improving the surface hardness of the steel sheet. To explain in more detail, a dislocation generally refers to a linear crystal defect, and the deformation of steel generally occurs when the position of the dislocation moves as a result of the iron atoms in the vicinity of the dislocation contained in the steel being rearranged by an external force or the like. Here, when an internal oxidation layer having a predetermined thickness, specifically a thickness of 3 μm or more from the surface of the steel sheet (if a plating layer is present on the surface of the steel sheet, the interface between the plating layer and the steel sheet) is formed in the surface layer of the steel sheet, many fine oxide particles are dispersed inside the internal oxidation layer, and such internal oxide particles become obstacles and inhibit the movement of dislocations, and as a result, it is believed that the surface hardness of the steel sheet is improved. On the other hand, merely forming an internal oxidation layer may not reliably prevent the occurrence of defects such as cracks and peeling, although the surface hardness is improved.

[0017] The present inventors have further studied and found that, when a certain amount of voids (air gaps) are present near the surface layer, the voids may become the starting point for the generation of defects such as peeling and cracks when the steel plate is subjected to some external force, and that the generation of such defects can be reliably suppressed by controlling the void area ratio in the region from the steel plate surface to a depth of 10 μm to 3.0% or less. Therefore, the high-strength steel plate according to the embodiment of the present invention can be used satisfactorily in applications such as high-strength steel plates for automobiles, which require excellent bending workability and high resistance to defects, and also in applications such as construction machine parts, which require excellent bending workability and wear resistance, such as the booms of cranes. The high-strength steel plate according to the embodiment of the present invention will be described in more detail below.

[0018] [Chemical composition at the center of plate thickness] First, the chemical composition of the plate thickness center portion will be described. In the plate thickness center portion, the chemical composition near the boundary with the soft surface portion may differ from that at a position sufficiently distant from the boundary due to diffusion of alloy elements with the soft surface portion. In such a case, the chemical composition of the plate thickness center portion described below refers to the chemical composition measured near the 1 / 2 position of the plate thickness. In addition, in the following description, the unit of content of each element, "%", means "mass%" unless otherwise specified. In addition, in this specification, "~" indicating a numerical range is used to mean that the numerical values ​​written before and after it are included as the lower and upper limits, unless otherwise specified.

[0019] [C:0.10~0.30%] Carbon (C) is an element effective in securing a predetermined amount of tempered martensite and improving the strength of the steel sheet. To fully obtain these effects, the C content is 0.10% or more. The C content may be 0.12% or more, 0.14% or more, 0.16% or more, or 0.18% or more. On the other hand, if C is contained excessively, the ductility and / or bending workability may decrease. Therefore, the C content is 0.30% or less. The C content may be 0.28% or less, 0.26% or less, 0.24% or less, or 0.22% or less.

[0020] [Si: 0.01-2.50%] Silicon (Si) is an element effective in ensuring hardenability. In addition, Si is also an element that suppresses alloying with Al. In order to fully obtain these effects, the Si content is 0.01% or more. The Si content may be 0.05% or more, 0.10% or more, 0.15% or more, or 0.30% or more. On the other hand, if Si is contained excessively, the center of the plate thickness becomes embrittled and bending workability may decrease. Therefore, the Si content is 2.50%. The Si content may be 2.20% or less, 2.10% or less, 2.00% or less, 1.80% or less, or 1.50% or less.

[0021] [Mn: 0.10~10.00%] Manganese (Mn) is an element that acts as a deoxidizer. Mn is also an element that is effective in improving hardenability. In order to fully obtain these effects, the Mn content is 0.10% or more. The Mn content may be 0.20% or more, 0.50% or more, 0.80% or more, or 1.00% or more. On the other hand, if Mn is contained excessively, coarse Mn oxides may form in the steel, which may reduce the elongation of the steel sheet. Therefore, the Mn content is 10.00% or less. The Mn content may be 9.00% or less, 8.00% or less, 6.00% or less, or 5.00% or less.

[0022] [P:0.100% or less] Phosphorus (P) is an element that is mixed in during the manufacturing process. The P content may be 0%. However, reducing the P content to less than 0.0001% requires time for refining, which leads to a decrease in productivity. Therefore, the P content may be 0.0001% or more, 0.0005% or more, 0.001% or more, or 0.005% or more. On the other hand, if P is contained excessively, it may segregate in the center of the thickness of the steel plate, reducing toughness. Therefore, the P content is 0.100% or less. The P content may be 0.080% or less, 0.060% or less, 0.040% or less, or 0.020% or less.

[0023] [S:0.0500% or less] Sulfur (S) is an element that is mixed in during the manufacturing process. The S content may be 0%. However, reducing the S content to less than 0.0001% requires time for refining, which leads to a decrease in productivity. Therefore, the S content may be 0.0001% or more, 0.0005% or more, or 0.0010% or more. On the other hand, if S is contained excessively, coarse MnS may be formed and the toughness of the steel plate may decrease. Therefore, the S content is 0.0500% or less. The S content may be 0.0400% or less, 0.0300% or less, 0.0200% or less, or 0.0100% or less.

[0024] [Al: 0-1.50%] Aluminum (Al) is an element that acts as a deoxidizer for steel and stabilizes ferrite. The Al content may be 0%, but in order to obtain such an effect, the Al content is preferably 0.001% or more. The Al content may be 0.01% or more, 0.02% or more, or 0.03% or more. On the other hand, if Al is contained excessively, coarse Al oxides may be generated, which may reduce the elongation of the steel sheet and / or may not be sufficient to generate tempered martensite. Therefore, the Al content is 1.50% or less. The Al content may be 1.40% or less, 1.30% or less, 1.00% or less, or 0.80% or less.

[0025] [N:0.0100% or less] Nitrogen (N) is an element that is mixed in during the manufacturing process. The N content may be 0%. However, reducing the N content to less than 0.0001% requires time for refining, which leads to a decrease in productivity. Therefore, the N content may be 0.0001% or more, 0.0005% or more, or 0.0010% or more. On the other hand, excessive N content may form coarse nitrides, which may reduce the bending workability and / or toughness of the steel sheet. Therefore, the N content is 0.0100% or less. The N content may be 0.0080% or less, 0.0060% or less, or 0.0050% or less.

[0026] [O:0.0060% or less] Oxygen (O) is an element that is mixed in during the manufacturing process. The O content may be 0%. However, reducing the O content to less than 0.0001% requires time for refining, which leads to a decrease in productivity. Therefore, the O content may be 0.0001% or more, 0.0005% or more, or 0.0010% or more. On the other hand, excessive O content may cause coarse inclusions to form and reduce the toughness of the steel plate. Therefore, the O content is 0.0060% or less. The O content may be 0.0050% or less, 0.0045% or less, or 0.0040% or less.

[0027] The basic chemical composition of the thickness center portion according to the embodiment of the present invention is as described above. Furthermore, the thickness center portion may contain at least one of the following optional elements in place of a part of the remaining Fe, if necessary. For example, the thickness center portion may contain at least one selected from the group consisting of Cr: 0-2.00%, Mo: 0-1.00%, and B: 0-0.0100%. The thickness center portion may also contain at least one selected from the group consisting of Ti: 0-0.30%, Nb: 0-0.30%, and V: 0-0.50%. The thickness center portion may also contain at least one selected from the group consisting of Cu: 0-1.00% and Ni: 0-1.00%. The thickness center portion may also contain at least one selected from the group consisting of Ca: 0-0.040%, Mg: 0-0.040%, and REM: 0-0.040%. These optional elements will be described in detail below.

[0028] [Cr:0~2.00%] Chromium (Cr) is an element effective in increasing the hardenability and increasing the strength of steel sheet. The Cr content may be 0%, but in order to obtain such an effect, the Cr content is preferably 0.001% or more. The Cr content may be 0.01% or more, 0.10% or more, or 0.20% or more. On the other hand, if Cr is excessively contained, Cr may segregate in the center of the thickness of the steel sheet to form coarse Cr carbides, which may reduce the elongation of the steel sheet. Therefore, the Cr content is preferably 2.00% or less. The Cr content may be 1.80% or less, 1.00% or less, or 0.50% or less.

[0029] [Mo:0~1.00%] Molybdenum (Mo) is an element effective for increasing the strength of steel sheet, similar to Cr. The Mo content may be 0%, but in order to obtain such an effect, the Mo content is preferably 0.001% or more. The Mo content may be 0.01% or more, 0.05% or more, or 0.10% or more. On the other hand, excessive Mo content may form coarse Mo carbides, which may reduce the cold workability of the steel sheet. Therefore, the Mo content is preferably 1.00% or less. The Mo content may be 0.90% or less, 0.80% or less, or 0.60% or less.

[0030] [B:0~0.0100%] Boron (B) is an element effective in increasing the strength of steel plate. The B content may be 0%, but in order to obtain such an effect, the B content is preferably 0.0001% or more. The B content may be 0.0005% or more, 0.0010% or more, or 0.0015% or more. On the other hand, if B is contained excessively, the toughness and / or weldability may decrease. Therefore, the B content is preferably 0.0100% or less. The B content may be 0.0080% or less, 0.0060% or less, or 0.0040% or less.

[0031] [Ti: 0~0.30%] Titanium (Ti) is an element effective in controlling the morphology of carbides and also promotes an increase in the strength of ferrite. The Ti content may be 0%, but in order to obtain these effects, the Ti content is preferably 0.001% or more. The Ti content may be 0.005% or more, 0.01% or more, or 0.02% or more. On the other hand, if Ti is contained excessively, coarse oxides or nitrides may be generated in the steel, which may reduce the workability of the steel sheet. Therefore, the Ti content is preferably 0.30% or less. The Ti content may be 0.20% or less, 0.15% or less, or 0.10% or less.

[0032] [Nb: 0~0.30%] Niobium (Nb) is an element effective for controlling the morphology of carbides, similar to Ti, and also contributes to improving the toughness of steel sheets by refining the structure through a pinning effect. The Nb content may be 0%, but in order to obtain these effects, the Nb content is preferably 0.001% or more. The Nb content may be 0.005% or more, 0.01% or more, or 0.02% or more. On the other hand, if Nb is contained excessively, a large number of fine and hard Nb carbides are precipitated, and the ductility decreases with an increase in the strength of the steel sheet, which may reduce the workability of the steel sheet. Therefore, the Nb content is preferably 0.30% or less. The Nb content may be 0.20% or less, 0.15% or less, or 0.10% or less.

[0033] [V:0~0.50%] Vanadium (V), like Ti and Nb, is an element effective in controlling the morphology of carbides, and is also an element that refines the structure by pinning effect and contributes to improving the toughness of the steel sheet. The V content may be 0%, but in order to obtain these effects, the V content is preferably 0.001% or more. The V content may be 0.005% or more, 0.01% or more, or 0.02% or more. On the other hand, if V is contained excessively, a large number of fine V carbides are precipitated, and the ductility decreases with the increase in the steel sheet strength, which may decrease the workability of the steel sheet. Therefore, the V content is preferably 0.50% or less. The V content may be 0.30% or less, 0.20% or less, or 0.10% or less.

[0034] [Cu: 0-1.00%] Copper (Cu) is an element effective in improving the strength of steel sheet. The Cu content may be 0%, but in order to obtain such an effect, the Cu content is preferably 0.001% or more. The Cu content may be 0.01% or more, 0.03% or more, or 0.05% or more. On the other hand, excessive Cu content may cause red shortness and reduce productivity in hot rolling. Therefore, the Cu content is preferably 1.00% or less. The Cu content may be 0.80% or less, 0.60% or less, or 0.40% or less.

[0035] [Ni:0~1.00%] Nickel (Ni) is an element that is effective in improving the strength of steel sheet, similar to Cu. The Ni content may be 0%, but in order to obtain such an effect, the Ni content is preferably 0.001% or more. The Ni content may be 0.01% or more, 0.03% or more, or 0.05% or more. On the other hand, excessive Ni content may decrease the ductility and may decrease the workability of the steel sheet. Therefore, the Ni content is preferably 1.00% or less. The Ni content may be 0.80% or less, 0.60% or less, or 0.40% or less.

[0036] [Ca: 0~0.040%] Calcium (Ca) is an element that can control the morphology of sulfides by adding a small amount. The Ca content may be 0%, but in order to obtain such an effect, the Ca content is preferably 0.0001% or more. The Ca content may be 0.0005% or more, 0.001% or more, or 0.005% or more. On the other hand, if Ca is contained excessively, coarse Ca oxides may be generated, which may reduce the workability of the steel sheet. Therefore, the Ca content is preferably 0.040% or less. The Ca content may be 0.030% or less, 0.020% or less, or 0.015% or less.

[0037] [Mg: 0~0.040%] Magnesium (Mg) is an element that can control the morphology of sulfides by adding a small amount, similar to Ca. The Mg content may be 0%, but in order to obtain such an effect, the Mg content is preferably 0.0001% or more. The Mg content may be 0.0005% or more, 0.001% or more, or 0.005% or more. On the other hand, excessive Mg content may generate coarse inclusions, which may reduce the workability of the steel sheet. Therefore, the Mg content is preferably 0.040% or less. The Mg content may be 0.030% or less, 0.020% or less, or 0.015% or less.

[0038] [REM:0~0.040%] Rare earth metals (REM) are elements that can control the morphology of sulfides by adding small amounts, similar to Ca and Mg. The REM content may be 0%, but in order to obtain such an effect, the REM content is preferably 0.0001% or more. The REM content may be 0.0005% or more, 0.001% or more, or 0.005% or more. On the other hand, excessive REM content may generate coarse inclusions and reduce the workability of the steel sheet. Therefore, the REM content is preferably 0.040% or less. The REM content may be 0.030% or less, 0.020% or less, or 0.015% or less. In this specification, REM is a collective term for 17 elements, namely, scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, and the REM content is the total content of these elements.

[0039] (others) Furthermore, the thickness center portion may intentionally or unavoidably contain the following elements, without impairing the effects of the present invention. These elements are W: 0-0.10%, Ta: 0-0.10%, Co: 0-0.50%, Sn: 0-0.050%, Sb: 0-0.050%, As: 0-0.050%, and Zr: 0-0.050%. The contents of these elements may be 0.0001% or more, or 0.001% or more, respectively.

[0040] In the sheet thickness center portion according to the embodiment of the present invention, the balance other than the above elements consists of Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, when the steel sheet or the sheet thickness center portion thereof is industrially manufactured.

[0041] [1.50≦[Si]+[Mn]+[Al]+[Cr]≦20.00] The chemical composition of the thickness center portion according to the embodiment of the present invention needs to satisfy the following formula. 1.50≦[Si]+[Mn]+[Al]+[Cr]≦20.00 In the formula, [Si], [Mn], [Al] and [Cr] are the contents (mass%) of each element. As explained above, in the high-strength steel sheet according to the embodiment of the present invention, the internal oxide formed in the outermost layer is extremely important in improving the surface hardness of the steel sheet. The internal oxide layer is formed in the outermost layer of the steel sheet mainly by the binding of relatively easily oxidized components in the steel sheet, such as Si, Mn, Al and Cr, with oxygen in the annealing atmosphere during the annealing treatment after cold rolling. Therefore, in order to form an internal oxide layer with a sufficient thickness to improve the surface hardness of the steel sheet, specifically to a thickness of 3 μm or more from the steel sheet surface, it is necessary that these elements are contained in the steel in a total amount of at least a certain amount. The chemical composition of the sheet thickness center according to the embodiment of the present invention is controlled so that the total content of Si, Mn, Al and Cr is 1.50% or more, that is, [Si] + [Mn] + [Al] + [Cr] ≧ 1.50, while controlling the content of each alloy element within the range explained above. By appropriately combining the chemical composition of the central part of the sheet thickness with the annealing conditions, it is possible to reliably form an internal oxide layer having a thickness of 3 μm or more. As a result, it is possible to achieve high surface hardness, suppress the occurrence of scratches on the steel sheet surface, and achieve excellent wear resistance.

[0042] The total content of Si, Mn, Al and Cr may be 1.60% or more, 1.70% or more, 1.80% or more, 1.90% or more, 2.00% or more, 2.20% or more, or 2.50% or more. On the other hand, if the total content of Si, Mn, Al and Cr is too high, it does not necessarily have a negative effect in terms of promoting the formation of internal oxides and increasing surface hardness, but the contents of each alloy element may become too high, which may deteriorate the related properties. Therefore, the total content of Si, Mn, Al and Cr is 20.00% or less. For example, the total content of Si, Mn, Al and Cr may be 15.00% or less, 12.00% or less, 10.00% or less, 9.00% or less, 8.00% or less, or 7.00% or less.

[0043] [Microstructure at the center of plate thickness] [Tempered martensite: 85% or more] The microstructure in the thickness center portion contains 85% or more tempered martensite in terms of area ratio. Tempered martensite is a high-strength and tough structure. In the embodiment according to the present invention, the steel sheet has the predetermined chemical composition described above, particularly a C content of 0.10% or more, and contains 85% or more tempered martensite in the thickness center portion, thereby making it possible to reliably achieve high tensile strength, specifically a tensile strength of 1250 MPa or more. The area ratio of tempered martensite may be 86% or more, 88% or more, or 90% or more. The upper limit of the area ratio of tempered martensite is not particularly limited and may be 100%. For example, the area ratio of tempered martensite may be 98% or less, 96% or less, or 94% or less.

[0044] [At least one of ferrite, bainite, pearlite, and retained austenite: less than 15% in total] The microstructure in the center of the sheet thickness may contain any other structure as long as it satisfies the requirement that it contains 85% or more of tempered martensite in terms of area ratio. Although not particularly limited, for example, it is preferable that the total area ratio of at least one of ferrite, bainite, pearlite, and retained austenite in the center of the sheet thickness is less than 15%.

[0045] Since ferrite is a soft structure, it is easily deformed and contributes to improving the ductility of the steel sheet. Therefore, from the viewpoint of improving the ductility of the steel sheet, the microstructure in the center of the sheet thickness may contain ferrite. However, since the interface between the hard structure of the tempered martensite and the soft structure of the ferrite can be the starting point of fracture, if ferrite is contained excessively, the hole expandability of the steel sheet may be reduced. In addition, since bainite is hard, it contributes to improving the strength of the steel sheet. Therefore, from the viewpoint of improving the strength of the steel sheet, the microstructure in the center of the sheet thickness may contain bainite. However, if bainite is contained excessively, although the strength of the steel sheet is improved, the uniformity of the microstructure may be reduced, which may reduce the hole expandability of the steel sheet. Bainite may be any of upper bainite having carbides between laths, lower bainite having carbides in the laths, bainitic ferrite without carbides, and granular bainitic ferrite in which the lath boundaries of bainite are restored and unclear, or a mixed structure thereof.

[0046] Pearlite is a hard structure in which soft ferrite and hard cementite are arranged in layers, and is a structure that contributes to improving the strength of the steel sheet. Therefore, from the viewpoint of improving the strength of the steel sheet, the microstructure in the center of the sheet thickness may contain pearlite. However, since the interface between the soft ferrite and the hard cementite can be the starting point of fracture, if pearlite is contained in excess, the hole expandability of the steel sheet may be reduced. In addition, retained austenite is a structure that contributes to improving the ductility of the steel sheet by the deformation-induced transformation (TRIP) effect. Therefore, from the viewpoint of improving the ductility of the steel sheet, the microstructure in the center of the sheet thickness may contain retained austenite. On the other hand, since retained austenite is transformed into martensite as quenched by deformation-induced transformation, if retained austenite is contained in excess, the hole expandability of the steel sheet may be reduced.

[0047] By controlling the total area ratio of at least one of ferrite, bainite, pearlite, and retained austenite to less than 15%, it is possible to reliably avoid the disadvantage of excessively containing these structures, more specifically, the decrease in hole expandability that is not related to the object of the present invention, while allowing the additional effects due to these structures to be fully expressed. The total area ratio of at least one of ferrite, bainite, pearlite, and retained austenite may be 0%, but may also be, for example, 1% or more, 3% or more, 4% or more, or 5% or more. In addition, the total area ratio of at least one of ferrite, bainite, pearlite, and retained austenite may be 14% or less, 12% or less, 11% or less, or 10% or less.

[0048] [As-quenched martensite: less than 5%] As-quenched martensite refers to martensite that has not been tempered, i.e., martensite that does not contain carbides. As-quenched martensite is a very hard structure. Therefore, the area ratio of as-quenched martensite may be 0%, but from the viewpoint of improving strength, it may be 1% or more or 2% or more. On the other hand, since as-quenched martensite is also a brittle structure, from the viewpoint of ensuring higher toughness, it is preferable that the area ratio of as-quenched martensite is less than 5%. The area ratio of as-quenched martensite may be 4% or less or 3% or less.

[0049] [Identification of microstructure at the center of plate thickness and calculation of area ratio] [Tempered martensite and bainite] The identification of the microstructure in the thickness center and the calculation of the area ratio are performed as follows. First, a sample having a thickness cross section parallel to the rolling direction of the steel sheet is taken, and the cross section is used as the observation surface. This observation surface is corroded with Nital reagent, and a 100 μm×100 μm region of the corroded observation surface centered at 1 / 4 of the sheet thickness from the steel sheet surface is used as the observation region. This observation region is observed at 1000 to 50000 times magnification using a field emission scanning electron microscope (FE-SEM). From the position of cementite contained in the structure in this observation region and the arrangement of cementite, tempered martensite and bainite are identified as follows. In tempered martensite, cementite exists inside the martensite lath, but there are two or more types of crystal orientations of martensite lath and cementite, and since cementite has multiple variants, tempered martensite can be identified. The area ratio of tempered martensite identified in this way is calculated by the point counting method (in accordance with ASTM E562). On the other hand, the state of existence of bainite may be that cementite or residual austenite is present at the interface of lath-shaped bainitic ferrite, or that cementite is present inside the lath-shaped bainitic ferrite. When cementite or residual austenite is present at the interface of lath-shaped bainitic ferrite, the interface of bainitic ferrite can be identified, and bainite can be identified. When cementite is present inside the lath-shaped bainitic ferrite, the crystal orientation relationship between bainitic ferrite and cementite is one type, and cementite has the same variant, and therefore bainite can be identified. The area fraction of bainite identified in this way is calculated by the point counting method.

[0050] [Ferrite] First, a sample having a thickness cross section parallel to the rolling direction of the steel sheet is taken, and the cross section is used as the observation surface. Of this observation surface, a 100 μm×100 μm region centered at 1 / 4 of the sheet thickness from the steel sheet surface is used as the observation region. This observation region is observed at 1000 to 50000 times magnification using a scanning electron microscope to obtain an electron channeling contrast image. The electron channeling contrast image is a method for detecting the crystal orientation difference within a crystal grain as a contrast difference, and the part with uniform contrast in this electron channeling contrast image is ferrite. The area ratio of ferrite identified in this way is calculated by the point counting method.

[0051] [Perlite] The observation area corroded with the Nital reagent described in relation to the tempered martensite and bainite is observed under an optical microscope at 1000 to 50000 times magnification, and the dark contrast area in the observation image is identified as pearlite. The area ratio of the identified pearlite is calculated by the point counting method.

[0052] [Retained austenite] The volume fraction of retained austenite is measured by X-ray diffraction. First, the surface of the steel plate from the surface to the 1 / 4 position of the plate thickness of the sample collected as described above is removed by mechanical polishing and chemical polishing to expose the surface of the steel plate from the surface to the 1 / 4 position of the plate thickness. The exposed surface is irradiated with MoKα radiation to obtain the integrated intensity ratio of the diffraction peaks of the (200) and (211) planes of the bcc phase and the (200), (220) and (311) planes of the fcc phase. The volume fraction of retained austenite is calculated from the integrated intensity ratio of the diffraction peaks. The general 5-peak method is used as the calculation method. The calculated volume fraction of retained austenite is determined as the area fraction of retained austenite.

[0053] [As-quenched martensite] First, the same observation surface as that used to identify ferrite is etched with Lepera liquid, and the same area as that used to identify ferrite is taken as the observation area. Martensite and retained austenite are not corroded by corrosion with Lepera liquid. Therefore, the observation area corroded by Lepera liquid is observed with FE-SEM, and the uncorroded area is identified as martensite and retained austenite. The total area ratio of the identified martensite and retained austenite is calculated by the point counting method. Next, the area ratio of the as-quenched martensite is determined by subtracting the area ratio of the retained austenite determined above from this total area ratio.

[0054] [Surface soft part] The soft surface portion formed on one or both sides of the center of the plate thickness has a thickness of more than 10 μm to 5.0% or less of the plate thickness, and has an average Vickers hardness (Hs) of 0.50 times or less of the average Vickers hardness (Hc) of the center of the plate thickness (i.e., Hs / Hc≦0.50). By having a thickness of more than 10 μm and satisfying Hs / Hc≦0.50, the effect of providing the soft surface portion on one or both sides of the steel plate can be reliably exhibited, and as a result, the bending workability of the steel plate can be significantly improved. For example, in order to further enhance the effect of improving the bending workability, the thickness of the soft surface portion may be 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, or 40 μm or more. The thickness of the soft surface portion may be 4.5% or less, 4.0% or less, 3.5% or less, 3.0% or less, or 2.5% or less of the plate thickness. When soft surface layers are formed on both sides of the thickness center, the thickness of the soft surface layer on one side may be the same as or different from the thickness of the soft surface layer on the other side. Similarly, in order to further enhance the effect of improving bending workability, the ratio (Hs / Hc) of the average Vickers hardness (Hs) of the soft surface layer to the average Vickers hardness (Hc) of the thickness center may be less than 0.50, 0.49 times or less, 0.48 times or less, 0.47 times or less, 0.46 times or less, or 0.45 times or less. The lower limit of Hs / Hc is not particularly limited, but for example, Hs / Hc may be 0.20 times or more, 0.25 times or more, or 0.30 times or more. When soft surface layers are formed on both sides of the thickness center, the Hs / Hc of the soft surface layer on one side may be the same as or different from the Hs / Hc of the soft surface layer on the other side.

[0055] In the present invention, the "thickness of the soft surface part", the "average Vickers hardness (Hc) of the central part of the plate thickness" and the "average Vickers hardness (Hs) of the soft surface part" are determined as follows, and the Vickers hardness test is performed in accordance with JIS Z 2244-1:2020. First, the Vickers hardness at the 1 / 2 position of the plate thickness of the steel plate is measured with an indentation load of 10 g, and then the Vickers hardness is measured at a total of three or more points, for example, five or ten points, with an indentation load of 10 g on a line perpendicular to the plate thickness and parallel to the rolling direction from that position, and the average value is determined as the average Vickers hardness (Hc) of the central part of the plate thickness. The distance between each measurement point is preferably four times or more than the indentation. The distance four times or more than the indentation means a distance four times or more than the length of the diagonal line of the rectangular opening of the indentation made by the diamond indenter when measuring the Vickers hardness. Next, the C concentration is measured in the depth direction from the surface using a glow discharge optical emission surface analyzer (GDS), and the region where the C concentration gradually increases from the surface until it becomes 1 / 2 of the average C concentration of the parent phase (C content at the center of the plate thickness) is defined as the surface soft part, and the thickness (μm) of the surface soft part and its proportion (%) in the plate thickness are determined. The Vickers hardness is measured at 10 random points in the surface soft part determined in this way with an indentation load of 10 g, and the average value is calculated to determine the average Vickers hardness (Hs) of the surface soft part. When the surface soft part is formed on both sides of the center of the plate thickness, the thickness and average Vickers hardness (Hs) of the surface soft part on the other side are determined by measuring in the same manner as described above.

[0056] [Microstructure of the soft surface layer] [Ferrite: 80% or more] The microstructure of the soft surface portion contains ferrite at an area ratio of 80% or more. Ferrite is a soft structure and is therefore easily deformed. Therefore, by containing ferrite at an area ratio of 80% or more in the soft surface portion, high bending workability can be achieved. The area ratio of ferrite may be 82% or more, 85% or more, 87% or more, or 90% or more. The upper limit of the area ratio of ferrite is not particularly limited and may be 100%. For example, the area ratio of ferrite may be 98% or less, 96% or less, or 94% or less.

[0057] [At least one of tempered martensite, bainite, and retained austenite: less than 20% in total] The microstructure of the soft surface portion may contain any other structure as long as it satisfies the requirement that it contains 80% or more ferrite in terms of area ratio. Although not particularly limited, for example, in the soft surface portion, the total area ratio of at least one of tempered martensite, bainite, and retained austenite is preferably less than 20%.

[0058] Tempered martensite and bainite are hard structures. In addition, the retained austenite is transformed into hard as-quenched martensite by processing-induced transformation. For this reason, from the viewpoint of further improving the bending workability of the steel sheet, the total area ratio of at least one of tempered martensite, bainite, and retained austenite may be, for example, 18% or less, 16% or less, 14% or less, or 12% or less. The total area ratio of at least one of tempered martensite, bainite, and retained austenite may be 0%, but may also be, for example, 1% or more, 3% or more, 5% or more, 8% or more, or 10% or more.

[0059] [Perlite: Less than 5%] As described above, the microstructure of the soft surface portion can achieve sufficiently high bending workability by containing ferrite at an area ratio of 80% or more, but from the viewpoint of further improving the bending workability of the steel sheet, it is preferable that the area ratio of pearlite, which is a hard structure, is less than 5%. The area ratio of pearlite may be 4.5% or less, 4% or less, or 3% or less. On the other hand, the lower limit of the area ratio of pearlite is not particularly limited and may be 0%. For example, the area ratio of pearlite may be 1% or more, or 2% or more.

[0060] [As-quenched martensite: less than 5%] As in the case of pearlite, from the viewpoint of further improving the bending workability of the steel sheet, the area ratio of the as-quenched martensite, which is a hard structure, is preferably less than 5%. The area ratio of the as-quenched martensite may be 4% or less or 3% or less. On the other hand, the lower limit of the area ratio of the as-quenched martensite is not particularly limited and may be 0%. For example, the area ratio of the as-quenched martensite may be 1% or more or 2% or more.

[0061] [Identification of microstructure in the soft surface layer and calculation of area ratio] The identification of the microstructure in the soft surface portion and the calculation of the area ratio are carried out as follows. First, a sample having a plate thickness cross section parallel to the rolling direction of the steel plate is taken, and the cross section is used as the observation surface. From this observation surface, multiple observation regions are selected at random so as not to be biased in the plate thickness direction within the range defined as the soft surface portion. The total area of ​​these observation regions is 2.0 × 10 -9 m 2 The identification of the microstructure other than the retained austenite and the calculation of its area ratio are the same as the identification of the microstructure in the center of the plate thickness and the calculation of its area ratio, except that the observation area is different.

[0062] [Retained austenite] The volume fraction of retained austenite in the soft surface region is obtained by obtaining crystal orientation information of the observation region using electron backscatter diffraction (EBSD). Specifically, first, a sample is taken with a cross section of the plate thickness parallel to the rolling direction of the steel plate. The cross section is used as the observation surface, and the observation surface is successively wet polished with emery paper, polished with diamond abrasive grains having an average particle size of 1 μm, and chemically polished. Next, multiple observation regions are randomly selected from the polished observation surface within the range defined as the soft surface region so as not to be biased in the plate thickness direction, and a total of 2.0 × 10 -9 m 2 The crystal orientation of the above regions is acquired at intervals of 0.05 μm. The software used to acquire the crystal orientation data is "OIM Data Collection TM (ver. 7)" manufactured by TSL Solutions Co., Ltd. The acquired crystal orientation information is separated into bcc and fcc phases using "OIM Analysis TM (ver. 7)" software manufactured by TSL Solutions Co., Ltd. This fcc phase is the retained austenite. The volume fraction of the retained austenite obtained in this way is determined as the area fraction of the retained austenite.

[0063] [Chemical composition of the soft surface layer] In the embodiment of the present invention, the chemical composition of the soft surface portion is basically the same as that of the center portion of the plate thickness except that the carbon concentration near the surface is lower. From the definition of the soft surface portion described above, the C content of the soft surface portion is 0.5 times or less the C content of the center portion of the plate thickness.

[0064] [Thickness of internal oxide layer: 3μm or more] In an embodiment of the present invention, the soft surface portion includes an internal oxide layer having a thickness of 3 μm or more from the surface of the steel sheet (the interface between the plated layer and the steel sheet when a plated layer is present on the surface of the steel sheet). It is considered that the inclusion of an internal oxide layer having a thickness of 3 μm or more pins the motion of dislocations contained in the steel by the numerous fine oxide particles present in the internal oxide layer, and as a result, the surface hardness of the steel sheet can be significantly improved. The thickness of the internal oxide layer may be 4 μm or more, 5 μm or more, 6 μm or more, 8 μm or more, or 10 μm or more. The upper limit of the thickness of the internal oxide layer is not particularly limited, but the thickness of the internal oxide layer may be, for example, 30 μm or less, 25 μm or less, or 20 μm or less.

[0065] The thickness of the internal oxide layer refers to the distance from the surface of the steel plate to the furthest position where the internal oxide exists when traveling from the surface of the steel plate in the thickness direction of the steel plate (the direction perpendicular to the surface of the steel plate). The thickness of the internal oxide layer is determined by taking a sample having a thickness cross section that is parallel to the rolling direction of the steel plate and includes the surface layer of the steel plate, and observing the cross section with an SEM. The depth to be measured is the region from the surface of the steel plate to 50 μm.

[0066] [Void area ratio near the surface: 3.0% or less] In an embodiment of the present invention, the void area ratio in the region from the surface of the steel sheet (the interface between the plating layer and the steel sheet when a plating layer is present on the surface of the steel sheet) to a depth of 10 μm is 3.0% or less. When a certain amount of voids (air gaps) are present near the surface, the voids may become the origin of defects due to peeling or the like when the steel sheet is subjected to some external force, for example, an external force such as bending. According to an embodiment of the present invention, by controlling the void area ratio in the region from the surface of the steel sheet to a depth of 10 μm to 3.0% or less, it is possible to reliably suppress the occurrence of such defects. The void area ratio may be 2.0% or less, 1.5% or less, or 1.0% or less. The lower limit of the void area ratio is not particularly limited and may be 0%. For example, the void area ratio may be 0.1% or more or 0.5% or more.

[0067] In the present invention, the void area ratio is determined as follows. First, the observation surface is mirror-finished by buffing to be used as the observation sample. Next, the surface of the observation sample or the area 5 μm below the interface between the plating layer and the base steel is photographed by SEM at a magnification of 9000 times, and a backscattered electron unevenness image is obtained for 15 adjacent consecutive fields of view, with a 10 μm × 10 μm area being one field of view. The area where unevenness is observed is analyzed by an energy dispersive X-ray spectrometer (EDS) to determine whether it is an inclusion or a void, and only the pure void portion is counted as a void, and the proportion of voids in the 10 μm × 150 μm area photographed by SEM is determined as the void area ratio.

[0068] Plate Thickness The high-strength steel plate according to the embodiment of the present invention generally has a plate thickness of 0.6 to 6.0 mm. Although not particularly limited, the plate thickness may be 1.0 mm or more, 1.2 mm or more, or 1.4 mm or more, and / or 5.0 mm or less, 4.0 mm or less, 3.0 mm or less, or 2.5 mm or less.

[0069] [Plating] The high-strength steel sheet according to the embodiment of the present invention may further include a plating layer on the surface of the soft surface portion for the purpose of improving corrosion resistance. The plating layer may be either a hot-dip plating layer or an electroplating layer. The hot-dip plating layer includes, for example, a hot-dip galvanizing layer, a hot-dip galvannealed layer, a hot-dip aluminum plating layer, a hot-dip Zn-Al alloy plating layer, a hot-dip Zn-Al-Mg alloy plating layer, a hot-dip Zn-Al-Mg-Si alloy plating layer, and the like. The electroplating layer includes, for example, an electrogalvanizing layer, an electrogalvanizing Zn-Ni alloy plating layer, and the like. Preferably, the plating layer is a hot-dip galvanizing layer, an alloyed hot-dip galvanizing layer, or an electrogalvanizing layer. The coating weight of the plating layer is not particularly limited and may be a general coating weight.

[0070] [Mechanical properties] According to the high-strength steel plate of the embodiment of the present invention, it is possible to achieve excellent mechanical properties, for example, a tensile strength of 1250 MPa or more. The tensile strength is preferably 1300 MPa or more, more preferably 1350 MPa or more. The upper limit is not particularly limited, but for example, the tensile strength may be 2000 MPa or less, 1800 MPa or less, or 1650 MPa or less. Similarly, according to the high-strength steel plate of the embodiment of the present invention, it is possible to achieve high hardness, more specifically, an average Vickers hardness (Hc) of the thickness center part of more than 400 Hv (i.e., an average Vickers hardness at the thickness 1 / 2 position) can be achieved. The average Vickers hardness (Hc) of the thickness center part is preferably 415 Hv or more, more preferably 430 Hv or more. Furthermore, according to the high-strength steel plate of the embodiment of the present invention, it is possible to achieve excellent bending workability, more specifically, a total elongation of 10% or more can be achieved. The total elongation is preferably 11% or more, more preferably 12% or more. The upper limit is not particularly limited, but for example, the total elongation may be 25% or less or 20% or less. The tensile strength and total elongation are measured by conducting a tensile test in accordance with JIS Z2241:2011 using a JIS No. 5 test piece taken in a direction parallel to the width direction of the steel plate (C direction).

[0071] The high-strength steel plate according to the embodiment of the present invention has improved bending workability, high resistance to the occurrence of defects, and can maintain good appearance properties, and is therefore very useful for use as, for example, a frame member of an automobile, which is particularly required for its appearance. In addition, since the high-strength steel plate has high surface hardness and therefore excellent wear resistance, it is also very suitable for applications requiring high bending workability and wear resistance in addition to high strength, such as the booms of cranes for construction machinery.

[0072] <Manufacturing method for high strength steel plate> Next, a preferred method for manufacturing a high-strength steel plate according to an embodiment of the present invention will be described. The following description is intended to exemplify a characteristic method for manufacturing a high-strength steel plate according to an embodiment of the present invention, but is not intended to limit the high-strength steel plate to one manufactured by the manufacturing method described below.

[0073] A method for producing a high strength steel plate according to an embodiment of the present invention includes: a hot rolling process including heating a slab having the chemical composition described above in relation to the center part of the plate thickness to a temperature of 1100-1250°C, then finish rolling the slab, immediately cooling the finish-rolled steel plate at an average cooling rate of 40°C / sec or more, and coiling the steel plate at a temperature of 590°C or less, wherein the end temperature of the finish rolling is 840-1050°C, the maximum temperature of the hot-rolled coil after coiling is controlled to 580°C or less, and the holding time in the temperature range from the maximum temperature to 500°C is limited to 4 hours or less; A step of pickling the obtained hot-rolled steel sheet; A cold rolling process in which the pickled hot-rolled steel sheet is cold-rolled at a rolling reduction of 30 to 80%; The obtained cold-rolled steel sheet was subjected to oxygen partial pressure P O2 Logarithm of (atm) logP O2 An annealing process including heating in an atmosphere of -20 to -16 at a temperature range of (Ac3-30) ° C or more; A cooling step comprising primarily cooling the cold-rolled steel sheet to a temperature of 680 to 780 ° C. at an average cooling rate of 0.5 to 20 ° C. / s, and then secondary cooling to a temperature of 25 to 600 ° C. at an average cooling rate of more than 20 ° C. / s; A tempering process including retaining the cold-rolled steel sheet in a temperature range of 100 to 400° C. for a time period of 150 to 1000 seconds. Each step will be described in detail below.

[0074] [Hot rolling process] [Heating the slab] First, a slab having the chemical composition described above in relation to the plate thickness center portion is heated. The slab used is preferably cast by a continuous casting method from the viewpoint of productivity, but may be manufactured by an ingot casting method or a thin slab casting method. The slab used contains a relatively large amount of alloying elements in order to obtain a high-strength steel plate. For this reason, it is necessary to heat the slab before subjecting it to hot rolling to dissolve the alloying elements in the slab. If the heating temperature is less than 1100°C, the alloying elements may not be sufficiently dissolved in the slab, leaving coarse alloy carbides, which may cause embrittlement cracking during hot rolling. For this reason, the heating temperature is preferably 1100°C or higher. The upper limit of the heating temperature is not particularly limited, but is preferably 1250°C or lower from the viewpoint of the capacity and productivity of the heating equipment.

[0075] [Rough rolling] In this method, for example, the heated slab may be subjected to rough rolling before finish rolling in order to adjust the plate thickness, etc. The conditions of the rough rolling are not particularly limited as long as the desired sheet bar dimensions can be secured.

[0076] [Finish rolling] The heated slab or the slab that has been rough-rolled as necessary is then subjected to finish rolling. Since the slab used as described above contains a relatively large amount of alloying elements, it is necessary to increase the rolling load during hot rolling. For this reason, it is preferable to perform hot rolling at a high temperature. In particular, the end temperature of the finish rolling is important in terms of controlling the metal structure of the steel sheet. If the end temperature of the finish rolling is low, the metal structure may become non-uniform and the formability may decrease. For this reason, the end temperature of the finish rolling is preferably 840°C or higher. On the other hand, in order to suppress the coarsening of austenite, it is preferable that the end temperature of the finish rolling is 1050°C or lower.

[0077] [Winding] Next, the finish-rolled steel sheet is immediately cooled at an average cooling rate of 40 ° C. / s or more, for example, 40 to 100 ° C. / s, and then coiled at a temperature of 590 ° C. or less. If the time until the start of cooling after finish rolling is long, the average cooling rate after finish rolling is slow, or the coiling temperature is high, the formation of an internal oxide layer is promoted in the surface layer of the hot-rolled steel sheet. Since the formed internal oxide layer cannot be sufficiently removed even by subsequent pickling, the cold rolling process is performed in a state including the internal oxide layer. In this case, voids are formed around the internal oxide during cold rolling, and the finally obtained steel sheet may not achieve a void area ratio of 3.0% or less. In order to reliably suppress the formation of such an internal oxide layer in the hot rolling process, the finish-rolled steel sheet needs to be immediately cooled at an average cooling rate of 40 ° C. / s or more, more specifically, it is cooled at an average cooling rate of 40 ° C. / s or more within 3 seconds after finish rolling. For the same reason, the coiling temperature needs to be 590 ° C. or less, and is preferably less than 550 ° C.

[0078] The maximum temperature of the hot-rolled coil (hot-rolled steel sheet) after coiling is controlled to 580°C or less, and the holding time in the temperature range from the maximum temperature of the hot-rolled coil to 500°C is limited to 4 hours or less. In order to suppress the formation of voids around the internal oxides during cold rolling, it is important to appropriately control the thermal history of the hot-rolled coil after coiling, in addition to controlling the cooling and coiling temperatures after finish rolling. For example, in order to ensure cold rolling properties, a heat retention treatment is sometimes performed on the hot-rolled coil after coiling. However, if such a heat retention treatment is performed at a high temperature and for a long treatment time, the oxide scale of the hot-rolled coil and the internal oxide layer on the surface may be formed thickly. In such a case, these cannot be sufficiently removed even by subsequent pickling, and uneven removal occurs along the width direction and length direction of the hot-rolled coil, which may cause the generation of voids. Since the transformation of the steel structure is an exothermic reaction, depending on the transformation speed, the temperature may rise above the coiling temperature even after coiling. Therefore, it is extremely important to appropriately monitor and control the thermal history of the hot-rolled coil after coiling to suppress the formation of excessive oxide scale and internal oxide layer. Preferably, the maximum temperature of the hot-rolled coil after coiling is controlled to 570°C or less, and the holding time in the temperature range from the maximum temperature of the hot-rolled coil to 500°C is limited to 3.5 hours or less. The method and place of measuring the temperature are not particularly limited, but for example, the temperature at a position about 25 m from the inner end of the hot-rolled coil toward the outer end of the hot-rolled coil in the longitudinal direction may be measured from the outside with a thermoviewer or by inserting a thermocouple into the hot-rolled coil.

[0079] [Pickling process] Next, the obtained hot-rolled steel sheet is pickled to remove the oxide scale formed on the surface of the hot-rolled steel sheet. The pickling may be performed once or may be performed multiple times to ensure the removal of the oxide scale, as long as the pickling is performed under conditions suitable for removing the oxide scale.

[0080] [Cold rolling process] The pickled hot-rolled steel sheet is cold-rolled at a reduction of 30 to 80% in the cold rolling process. By setting the reduction of cold rolling to 30% or more, the shape of the cold-rolled steel sheet can be kept flat, and the decrease in ductility in the final product can be suppressed. The reduction of cold rolling is preferably 50% or more. On the other hand, by setting the reduction of cold rolling to 80% or less, it is possible to prevent the rolling load from becoming excessive and making rolling difficult. The reduction of cold rolling is preferably 70% or less. The number of rolling passes and the reduction of each pass are not particularly limited, and may be appropriately set so that the reduction of the entire cold rolling is within the above range.

[0081] [Annealing process] [Oxygen partial pressure in the atmosphere P O2 Logarithm of (atm) logP O2 :-20~-16] [Annealing temperature range: (Ac3-30)℃ or higher] The obtained cold-rolled steel sheet is, for example, in a heating furnace and a soaking furnace of a continuous annealing line, subjected to the oxygen partial pressure P O2 Logarithm of (atm) logP O2 While maintaining the temperature at -20 to -16, the steel is heated in a temperature range of (Ac3-30)° C. or higher for annealing. Here, the Ac3 point can be approximately calculated based on the following formula. Ac3=937.2-436.5×[C]+56×[Si]-19.7×[Mn]-16.3×[Cu]-26.6×[Ni]-4.9×[ Cr]+38.1×[Mo]+124.8×[V]+136.3×[Ti]-19.1×[Nb]+198.4×[Al]+3315×[B] In the formula, [C], [Si], [Mn], [Cu], [Ni], [Cr], [Mo], [V], [Ti], [Nb], [Al] and [B] are the contents (mass%) of each element in the steel plate.

[0082] By annealing in a relatively oxidizing atmosphere and at high temperatures as described above, the surface layer of the steel sheet is softened by decarburization to form a desired soft surface layer, and oxygen from the atmosphere is diffused into the steel to form a desired internal oxide layer near the surface of the steel sheet. More specifically, by heating in a temperature range of (Ac3-30)°C or higher in a heating furnace and a soaking furnace, decarburization of the surface layer of the steel sheet progresses and the carbon content of the surface layer decreases. The reduction in the carbon content of the surface layer reduces the hardenability of the surface layer, making it possible to obtain an appropriate amount of ferrite in the surface layer. In order to promote such decarburization, the oxygen partial pressure P O2 (atm) must be controlled within an appropriate range. O2 Logarithm of logP O2 When logP is -20 or more, the oxygen potential becomes sufficiently high and decarburization proceeds. In addition, in such an oxidizing atmosphere, the diffusion of oxygen from the atmosphere into the steel is promoted, and the internal oxidation of Si, Al, Mn, Cr, etc. present in the vicinity of the surface of the steel sheet proceeds, and an internal oxide layer having a sufficient thickness, more specifically a thickness of 3 μm or more, can be formed in the vicinity of the surface of the steel sheet. O2 is preferably -19 or more. On the other hand, logP O2 By controlling the logP to -16 or less, it is possible to suppress excessive decarburization and internal oxidation caused by an excessively high oxygen potential. This makes it possible to reliably obtain the desired soft surface layer and internally oxidized layer. In addition, the oxidation of not only Si, Al, Mn, etc., but also the base steel sheet itself is suppressed, making it easier to obtain the desired surface condition of the steel sheet. O2 is preferably −17 or less. According to the present method, since an internal oxide layer is formed in the annealing step after the cold rolling step, voids are not formed around the internal oxide during cold rolling, as compared with the case where an internal oxide layer is formed in the hot rolling step, and a void area ratio of 3.0% or less can be reliably achieved in the finally obtained steel sheet.

[0083] In addition, by heating in the annealing process at a temperature range of (Ac3-30) ° C. or higher, austenite is generated during annealing, and a predetermined amount of tempered martensite can be easily obtained as the final structure in the center of the plate thickness. This makes it possible to achieve the desired high strength of the steel plate. On the other hand, if the annealing temperature range is too high, the productivity decreases, although there is no problem in terms of the properties of the steel plate. For this reason, the heating temperature range of the annealing process is preferably 1100 ° C. or lower, and more preferably 950 ° C. or lower. For example, when the surface soft portion is formed only on one side of the steel plate, two cold-rolled steel plates may be stacked in the main annealing process and annealed under the above-described conditions to decarburize and soften only one surface layer of the steel plate.

[0084] [Cooling process] Following the annealing process, in order to form the desired structure in the soft surface portion and the center portion of the sheet thickness, the obtained cold-rolled steel sheet is primarily cooled to a temperature of 680 to 780°C at an average cooling rate of 0.5 to 20°C / s, and then secondarily cooled to a temperature of 25 to 600°C at an average cooling rate of more than 20°C / s.

[0085] [Primary cooling: Cool to 680-780℃ at an average cooling rate of 0.5-20℃ / sec] By setting the average cooling rate of the primary cooling to 20°C / sec or less, the generation of ferrite in the soft surface portion can be promoted. The upper limit of the average cooling rate in the primary cooling is set to ensure the effect of dividing the cooling process into two stages, the primary cooling and the secondary cooling. From this viewpoint, the average cooling rate of the primary cooling is preferably 18°C / sec or less, more preferably 16°C / sec or less. By setting the cooling process to such two stages, for example, it is possible to achieve a higher ferrite area ratio without generating pearlite or the like in the soft surface portion or while suppressing the generation of pearlite or the like. On the other hand, by setting the average cooling rate of the primary cooling to 0.5°C / sec or more, excessive progress of ferrite transformation and pearlite transformation not only in the soft surface portion but also in the center of the plate thickness is suppressed, so that a predetermined amount of tempered martensite can be easily obtained in the center of the plate thickness. The average cooling rate of the primary cooling is preferably 1°C / sec or more, more preferably 2°C / sec or more. Furthermore, by setting the cooling end temperature of the primary cooling to 680°C or higher, it is possible to suppress the generation of a large amount of structures other than ferrite in the soft surface portion, which would otherwise cause a decrease in the bending workability of the steel sheet. The cooling end temperature of the primary cooling is preferably 700°C or higher. On the other hand, by setting the cooling end temperature of the primary cooling to 780°C or lower, it is possible to promote the generation of ferrite in the soft surface portion.

[0086] [Secondary cooling: Cool to a temperature of 25-600°C at an average cooling rate of more than 20°C / sec] The average cooling rate and cooling stop temperature of the secondary cooling are particularly important in forming as-quenched martensite to obtain a predetermined amount of tempered martensite in the center of the plate thickness. As-quenched martensite is generated by transformation using a small amount of dislocations present in austenite grains before transformation as nuclei in the temperature range of 25 to 600 ° C. After the primary cooling, by setting the average cooling rate until the temperature range of 25 to 600 ° C. is reached to more than 20 ° C. / sec, it is possible to suppress the disappearance of dislocations contained in austenite grains before transformation. As a result, it is possible to reliably achieve 85% or more of tempered martensite in the final structure of the center of the plate thickness. The average cooling rate of the secondary cooling is preferably 23 ° C. / sec or more. In addition, the cooling stop temperature of the secondary cooling is 25 ° C. or more, but from the viewpoint of further improving productivity, it is preferably 100 ° C. or more. On the other hand, by setting the cooling stop temperature to 600 ° C. or less, it is possible to reliably generate a predetermined amount of martensite while suppressing the generation of ferrite, bainite, and pearlite in the center of the plate thickness. The cooling stop temperature of the secondary cooling is preferably 500° C. or lower.

[0087] [Tempering process] The cold-rolled steel sheet after the cooling process mainly contains as-quenched martensite in the center of the thickness. Therefore, it is necessary to temper this as-quenched martensite to tempered martensite in the next tempering process. More specifically, in the tempering process, the cold-rolled steel sheet is held in a temperature range of 100 to 400 ° C for a time of 150 to 1000 seconds, thereby tempering the as-quenched martensite in the center of the thickness to tempered martensite, and the workability of the steel sheet can be improved compared to the case where the center of the thickness mainly contains as-quenched martensite. By setting the holding temperature to 100 ° C or more, the effect of tempering can be reliably obtained. On the other hand, by setting the holding temperature to 400 ° C or less, it is possible to suppress excessive tempering and maintain the strength of the steel sheet at a high level. In addition, by setting the holding time to 150 seconds or more, it is possible to reliably obtain a predetermined amount of tempered martensite. On the other hand, from the viewpoint of productivity, it is preferable that the holding time is 1000 seconds or less.

[0088] [Plating and surface treatment] When hot-dip galvanizing is performed on a steel sheet as a plating process, the steel sheet is heated or cooled to a temperature that is at least 40°C lower than the temperature of the galvanizing bath and at most 50°C higher than the temperature of the galvanizing bath, and the steel sheet is passed through the galvanizing bath. By such hot-dip galvanizing, a steel sheet having a hot-dip galvanized layer on the surface, i.e., a hot-dip galvanized steel sheet, is obtained. The hot-dip galvanized layer has a chemical composition of, for example, 7 to 15 mass% Fe, and the balance Zn, Al, and impurities. The hot-dip galvanized layer may be a zinc alloy.

[0089] When alloying treatment is performed after hot-dip galvanizing treatment, for example, the hot-dip galvanized steel sheet is heated to a temperature of 460°C or more and 600°C or less. If the heating temperature is less than 460°C, alloying may be insufficient. On the other hand, if the heating temperature is more than 600°C, alloying may be excessive, resulting in deterioration of corrosion resistance. By such alloying treatment, a steel sheet having an alloyed hot-dip galvanized layer on the surface, i.e., an alloyed hot-dip galvanized steel sheet, is obtained.

[0090] The steel sheet may be subjected to a plating treatment such as electroplating or vapor deposition plating, and further may be subjected to an alloying treatment after the electroplating. The steel sheet may also be subjected to a surface treatment such as formation of an organic film, film lamination, organic salt or inorganic salt treatment, or non-chromium treatment.

[0091] [Post-process tempering] Finally, the steel sheet may be optionally subjected to additional tempering in order to adjust the strength, etc. of the steel sheet. Such tempering is not particularly limited, and may be performed, for example, by holding the steel sheet in a temperature range of 200 to 500°C for 2 seconds or more.

[0092] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. EXAMPLES

[0093] [Example A] In this example, first, a continuous cast slab having a thickness of 20 mm and having the chemical composition shown in Table 1 was heated to a predetermined temperature in the range of 1100 to 1250 ° C., and hot rolling was performed under conditions such that the end temperature of the finish rolling was 840 to 1050 ° C., and the slab was cooled at an average cooling rate of 40 ° C. / s within 3 seconds after the finish rolling, and then coiled at the coiling temperature shown in Table 2. The maximum temperature of the hot rolled coil after coiling was controlled to 580 ° C. or less, and the holding time in the temperature range from the maximum temperature of the hot rolled coil to 500 ° C. was 3.5 hours or less. The temperature of the hot rolled coil was measured by inserting a thermocouple at a position about 25 m from the inner end of the hot rolled coil toward the outer end in the length direction. Next, the obtained hot rolled steel sheet was pickled, and then cold rolling was performed at the reduction rate shown in Table 2. Next, the obtained cold rolled steel sheet was annealed under the conditions shown in Table 2 to decarburize and soften the surface layer of the steel sheet, and then cooling and tempering were performed under the conditions shown in Table 2. In Table 3, the steel sheets with the surface softened portion on only one side are obtained by stacking two cold-rolled steel sheets and annealing them during the annealing process to decarburize and soften only one surface layer of the steel sheet. Finally, the steel sheet product was obtained by performing plating, alloying, and additional tempering treatment as necessary. When the chemical composition of the portion corresponding to the center of the sheet thickness of the sample taken from the obtained steel sheet was analyzed, there was no change from the chemical composition shown in Table 1.

[0094] [Table 1]

[0095] [Table 2]

[0096] The properties of the obtained steel sheets were measured and evaluated by the following methods.

[0097] [Thickness of the soft surface layer, average Vickers hardness (Hc) at the center of the plate thickness, and average Vickers hardness (Hs) at the soft surface layer] The "thickness of the soft surface part", "average Vickers hardness (Hc) at the center of the plate thickness" and "average Vickers hardness (Hs) at the soft surface part" were determined as follows, and the Vickers hardness test was performed in accordance with JIS Z 2244-1:2020. First, the Vickers hardness was measured at 1 / 2 the plate thickness of the steel plate with an indentation load of 10 g, and then the Vickers hardness was measured at a total of five points from that position in a direction perpendicular to the plate thickness and on a line parallel to the rolling direction with an indentation load of 10 g, and the average value was determined as the average Vickers hardness (Hc) at the center of the plate thickness. The distance between each measurement point was set to a distance of at least four times the indentation. Next, the C concentration was measured in the depth direction from the surface using GDS, and the area from the surface where the C concentration gradually increases until it becomes 1 / 2 of the average C concentration of the parent phase was defined as the soft surface part, and the thickness (%) of the soft surface part was determined. The Vickers hardness was measured at 10 random points in the soft surface portion thus determined with an indentation load of 10 g, and the average value was calculated to determine the average Vickers hardness (Hs) of the soft surface portion.

[0098] [Internal oxide layer thickness] The thickness of the internal oxide layer was determined by taking a sample having a thickness cross section parallel to the rolling direction of the steel sheet and including the surface layer of the steel sheet, observing the cross section with an SEM, and measuring the distance from the surface of the steel sheet to the farthest position where the internal oxide existed in the thickness direction of the steel sheet (direction perpendicular to the surface of the steel sheet). The measurement depth was the region from the surface of the steel sheet to 50 μm.

[0099] [Void area ratio near the surface] The void area ratio near the surface was determined as follows. First, the surface to be observed was polished to a mirror finish by buffing to prepare the observation sample. Next, an image was taken with an SEM at a magnification of 9000x, centered on the surface of the observation sample or 5 μm below the interface between the plating layer and the base steel, and a backscattered electron unevenness image was obtained for 15 consecutive adjacent fields of view, with each field of view being a 10 μm × 10 μm area. The area where unevenness was observed was analyzed with EDS to determine whether it was an inclusion or a void, and only pure voids were counted as voids, and the proportion of voids in the 10 μm × 150 μm area photographed with the SEM was determined to be the void area ratio.

[0100] [Tensile strength and total elongation] The tensile strength TS and the total elongation t-El were measured by conducting a tensile test in accordance with JIS Z2241:2011 using a JIS No. 5 test piece taken in a direction parallel to the sheet width direction of the steel sheet (C direction).

[0101] [Evaluation of bending workability] The bending workability was evaluated by measuring the bending angle α (°) using a bending test in accordance with VDA (German Automotive Industry Association) standard 238-100:2017-04.

[0102] [Evaluation of defect occurrence] The occurrence of defects was evaluated by whether or not microcracks 3μm or more in length occurred around the indentation when 10 points at a depth of 5μm from the surface of the steel sheet (if a plating layer exists on the surface of the steel sheet, the interface between the plating layer and the steel sheet) were pressed down with a Vickers hardness tester (load 100g) at room temperature. Specifically, the evaluation was made as whether or not microcracks occurred, with the case where no microcracks occurred being passed (OK) and the case where microcracks occurred being failed (NG).

[0103] A high-strength steel sheet with improved bending workability and capable of suppressing the occurrence of defects was evaluated as one with a tensile strength of 1250 MPa or more, a total elongation of 10% or more, a bending angle of 70° or more, and no occurrence of microcracks. The results are shown in Table 3. In Table 3, for steel sheets in which soft surface portions are formed on both sides of the center of the sheet thickness, only values ​​for the soft surface portion and the internal oxide layer on one side are shown. However, since these steel sheets are manufactured by carrying out the same treatment on both sides, the values ​​for the soft surface portion and the internal oxide layer are substantially the same on both sides of the steel sheet, and it has been confirmed that these values ​​are actually the same on both sides of some steel sheets.

[0104] [Table 3-1]

[0105] [Table 3-2]

[0106] Referring to Table 3, in Comparative Example 22, the total area ratio of the tempered martensite and the as-quenched martensite was relatively high, but the tensile strength was reduced because the C content was low. In Comparative Example 23, the tensile strength was improved because the C content was high, but the bending workability was reduced. In Comparative Example 24, the bending workability was reduced because the Si content was high. In Comparative Example 25, the bending workability was reduced because the Mn content was high. In Comparative Example 26, it is considered that coarse Al oxides were generated because the Al content was high, and as a result, the bending workability was reduced. In Comparative Example 27, it is considered that coarse Cr carbides were generated because the Cr content was high, and as a result, the bending workability was reduced. In Comparative Example 28, the total content of Si, Mn, Al, and Cr was low, so that the internal oxide layer could not be sufficiently formed, and as a result, the surface hardness was reduced and the occurrence of microcracks was observed. In Comparative Example 29, the coiling temperature was high, so that the internal oxide layer was formed during the hot rolling process. For this reason, it is believed that voids were formed around the internal oxides during the subsequent cold rolling, and as a result, the void area ratio near the surface layer in the final steel sheet product could not be sufficiently reduced, and the occurrence of microcracks was observed. In Comparative Example 30, the stop temperature of the secondary cooling was high, so the desired amount of tempered martensite was not generated in the center of the sheet thickness, and as a result, the tensile strength was reduced. In Comparative Example 31, the average cooling rate of the primary cooling was too fast, so ferrite could not be sufficiently generated in the soft surface portion, and as a result, the Hs / Hc value increased and bending workability was reduced. In Comparative Example 32, the oxygen partial pressure P O2 Logarithm of logP O2 Because the temperature was low, decarburization was not promoted and the internal oxide layer could not be formed sufficiently, resulting in a decrease in surface hardness and the occurrence of microcracks.

[0107] In contrast, in Examples 1 to 21, the center portion of the sheet thickness and the soft surface portion having a predetermined chemical composition and / or microstructure were controlled so that their average Vickers hardness satisfied Hs / Hc≦0.50, and further, the internal oxide layer was made to be 3 μm or more thick from the steel sheet surface while controlling the void area ratio near the surface to 3.0% or less. This made it possible to improve bending workability despite the high strength of 1250 MPa or more, and furthermore, to significantly suppress the occurrence of defects on the steel sheet surface.

[0108] [Example B] In this example, the influence of controlling the thermal history after coiling on the properties of the resulting steel sheet was investigated. Specifically, Example 16 in Table 3 was used as a reference (maximum temperature of the hot-rolled coil after coiling: 567°C and holding time in the temperature range from the maximum temperature to 500°C: 3.5 hours), and in Comparative Examples 33 and 34, the maximum temperature of the hot-rolled coil after coiling and the holding time in the temperature range from the maximum temperature to 500°C were changed. Other manufacturing conditions in Comparative Examples 33 and 34 were the same as in Example 16. The results are shown in Table 4.

[0109] [Table 4]

[0110] Referring to Table 4, in Example 16, in which the maximum temperature of the hot-rolled coil after coiling was 580°C or less and the holding time in the temperature range from the maximum temperature to 500°C was 4 hours or less, the void area ratio in the vicinity of the surface layer in the final product steel sheet was 0.0%, and therefore sufficiently reduced to 3.0% or less, as already shown in Table 3. As a result, the occurrence of microcracks was not observed in Example 16. On the other hand, in Comparative Example 33, in which the maximum temperature of the hot-rolled coil after coiling was over 580°C, and Comparative Example 34, in which the holding time in the temperature range from the maximum temperature to 500°C was over 4 hours, the void area ratio in the vicinity of the surface layer could not be controlled to 3.0% or less, and the occurrence of microcracks was observed. This result is considered to be due to the fact that an internal oxide layer was formed during the hot rolling process due to the high maximum temperature or long holding time of the hot-rolled coil after coiling, and voids were formed around the internal oxide during the subsequent cold rolling.

Claims

1. A high-strength steel plate including a plate thickness center portion and a surface soft portion formed on one side or both sides of the plate thickness center portion, The thickness center portion is, in mass%, C: 0.10-0.30%, Si: 0.01-2.50%, Mn: 0.10-10.00%, P: 0.100% or less, S: 0.0500% or less, Al: 0 to 1.50%, N: 0.0100% or less, O: 0.0060% or less, Cr: 0-2.00%, Mo: 0-1.00%, B: 0 to 0.0100%, Ti: 0 to 0.30%, Nb: 0 to 0.30%, V: 0-0.50%, Cu: 0 to 1.00%, Ni: 0 to 1.00%, Ca: 0-0.040%, Mg: 0 to 0.040%, REM: 0 to 0.040%, and The balance is composed of Fe and impurities. A chemical composition satisfies 1.50≦[Si]+[Mn]+[Al]+[Cr]≦20.00, in which [Si], [Mn], [Al] and [Cr] are the contents (mass%) of each element, In terms of area ratio, Tempered martensite: having a microstructure containing 85% or more; The surface soft portion has a thickness of more than 10 μm to 5.0% or less of the plate thickness, In terms of area ratio, Ferrite: having a microstructure containing 80% or more, The high-strength steel plate includes an internal oxide layer having a thickness of 3 μm or more from a surface thereof, The average Vickers hardness (Hc) of the plate thickness center portion and the average Vickers hardness (Hs) of the surface layer soft portion satisfy Hs / Hc≦0.50, A high-strength steel plate, wherein a void area ratio in a region from the surface of the high-strength steel plate to a depth of 10 μm is 3.0% or less.

2. The thickness center portion has an area ratio of Tempered martensite: 85% or more, At least one of ferrite, bainite, pearlite, and retained austenite: less than 15% in total; and The high strength steel plate according to claim 1, having a microstructure consisting of less than 5% as-quenched martensite.

3. The surface soft portion has an area ratio of Ferrite: 80% or more, At least one of tempered martensite, bainite, and retained austenite: less than 20% in total; Perlite: less than 5%; The high strength steel plate according to claim 1 or 2, having a microstructure consisting of as-quenched martensite: less than 5%.

4. The high-strength steel plate according to claim 1 or 2, further comprising a hot-dip galvanized layer, a galvannealed layer, or an electrolytic galvanized layer on a surface of the soft surface portion.

Citation Information

Patent Citations

  • High-strength cold-rolled steel sheet, high-strength galvanized steel sheet, and high-strength alloying hot-dip galvanized steel sheet, excellent in bendability, and method for manufacturing the same

    JP2013163827A

  • High-strength hot-rolled steel plate with excellent bendability and wear resistance, and method for manufacturing the same

    JP2014227583A

  • Super-high strength cold-rolled steel sheet having excellent bending properties

    WO2011105385A1

  • High-strength plated steel sheet having superior plating properties, workability, and delayed fracture resistance, and method for producing same

    WO2015005191A1

  • High-strength alloyed hot-dipped galvanized steel sheet having excellent workability and delayed fracture resistance, and method for producing same

    WO2015146692A1